The Relationship between Cortisol and Bone Mineral Density in Competitive Male Cyclists. (29th May 2013) - Mathis, Shannon L.; Farley, Richard S.; Fuller, Dana K.; Jetton, Amy E.; Caputo, Jennifer L.
Abstract : Objective . The purpose of this study was to determine whether race day cortisol was related to bone mineral density (BMD) in competitive male cyclists. A secondary purpose was to determine additional factors associated with BMD in competitive male cyclists. Methods . Measurements of lumbar spine and hip BMD were performed in 35 male competitors in a state championship cycling time trial event. Salivary cortisol was measured 10 minutes prior to the start of the race and 5 minutes after race finished. Participants reported daily calcium intake, age, years of bike training, races per season, and average weekly minutes spent riding a bike, weight training, and running on a survey. Results . Cortisol level increased significantly from pre- to postcompetition but was not significantly associated with BMD. Increased weekly minutes of weight training was associated with higher BMD of the lumbar spine and the hip. The increased number of years of cycling experience was associated with lower BMD of the femoral neck. Increased daily calcium intake was associated with higher BMD of the lumbar spine and femoral neck. Conclusions . Findings indicate that cyclists should participate in weight training and increase calcium intake in order to increase or maintain BMD of the lumbar spine and hip.